PENGEMBANGAN MEDIA PEMBELAJARAN ILMU TAJWID BERBASIS ANDROID STUDIO UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA SANTRI TPA - Hasan, Wirahamdi; Suryadi, Ahmad (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
Learning Media holds the most important aspect in supporting the teaching and learning process, especially for Qur'anic Tajweed lessons. For a Muslim, learning Tajweed Al-Qur'an is an obligation that must be done. However, student motivation is minimal due to lack of time and learning media that only use conventional media such as books and monotonous learning methods. Therefore, a Tajweed Application accompanied by an Android-based Al-Qur'an Tajweed learning media Educational Game will be able to increase interest and desire to learn the Qur'an to learn complete and interactive Al-Qur'an Tajweed. The authors of this study used a design model with the Unified Modeling Language (UML) consisting of Use Case Diagrams, Activity Diagrams, and Sequence Diagrams. The results of this study produced an android-based tajweed application learning product (MATA) on tajweed learning at TPA Nurul Iman using the 4-D development model by going through 4 procedures, namely define, design, develop and disseminate which were carried out on research subjects at TPA Nurul Iman Jakarta. In addition, the calculation of the effectiveness test using the N-Gain formula obtained an increase of 0.70, which means that the average increase is in the effective category, namely> 0.56. These results show that the MATA application on android-based tajweed learning is effective in learning.